Analysis of the partial discharge pulse propagation in the stator winding of a synchronous machine (2015)
In this paper, a study of the propagation of partial discharge pulses in the stator winding of a synchronous machine is presented. This study was performed by injecting artificial partial discharge pulses in the stator winding of a 2.4 kV/210 kVA salient-pole synchronous machine. It was found that the propagation of the partial-discharge PD signals is presented in two modes: the slow mode, in which the coil acts as a transmission line; and the fast mode, in which the pulse propagates through the overhangs. The fast mode is due to capacitive and inductive couplings in the overhangs. In the slow mode, a PD signal manifests itself at the generator terminals after a transit time that depends on the distance traveled by the pulse. A strong positive linear correlation was observed between the arrival time in the slow mode and the length traveled by the pulse in this mode. The DC ohmic resistance between the injection point and the measurement point was used to represent the distance traveled by the pulse in the slow mode. The capacitive and inductive couplings also cause a crosstalk between the phases. As a consequence, a PD signal can be measured at different phases to the origin phase. In the slow mode, the signal will suffer attenuation in amplitude due to the dispersion and the absorption of energy while it propagates in the slow mode.